Leslie Stewart's S Revenge In Sidney Sheldon’s The Best Laid Plans - Skarmelia Goresti Getsemani Dala; Putut Handoko; Haryono (Menulis: Jurnal Penelitian Nusantara, 2025)
This study investigates the portrayal of revenge through Leslie Stewart’s character in Sidney Sheldon’s The Best Laid Plans, with particular focus on the dimension of being driven by pride. Drawing on Böhm and Kaplan’s theoretical framework of revenge, this qualitative research employs textual analysis to examine how Leslie’s wounded pride becomes the central motivation behind her acts of retaliation. The findings reveal that Leslie’s pride, rooted in her identity as a supportive partner and professional woman, is deeply injured by Oliver Russell’s betrayal. Her sense of dignity and public image is further attacked through humiliation, slander, and rejection, which transforms her personal pain into a calculated quest for revenge. Leslie’s actions illustrate that pride-driven revenge is not limited to emotional satisfaction but functions as a symbolic restoration of honor, particularly when enacted in the public sphere. Ultimately, the study concludes that Leslie Stewart’s revenge exemplifies how betrayal and humiliation intertwine with pride to shape a complex narrative of vengeance, where reclaiming dignity becomes as important as punishing the offender.